20-40 yaş arası çalışan ve çalışmayan kadınların spor yapmalarını etkileyen bazı faktörlerin incelenmesi (Sivas il merkezi örneği) - (:unkn) unknown (My University, 2009)
Bu araştırma; sağlıklı, sosyal ve kültürel alanda çağdaş bir toplum yaratmada kadınlarımızın spor yapmasının öneminden hareketle, çalışan ve çalışmayan kadınların spor yapma durumlarını araştırmak ve kadınlarımızın daha fazla spora yönlenmesini sağlamak amacıyla yapılmıştır. Araştırmanın örneklemi evreni temsil edecek şekilde Sivas il merkezinde yaşayan, 20–40 yaş arası özel-kamu kurum ve kuruluşlarında çalışan 122 ve çalışmayan 196 olmak üzere toplam 318 kadından oluşmuştur. Araştırmada veriler araştırmacı tarafından hazırlanan 34 sorudan oluşan anket formu aracılığı ile toplanmıştır. Araştırmada elde edilen verilerle ilgili istatistiksel işlemlerde SPSS (11.0 ver.) paket programı kullanılmıştır. Grupların frekans dağılımı arasındaki farklılığın önemli olup olmadığını açığa çıkarmak için X2 (Chi-Square) istatistik tekniği uygulanmıştır. Araştırmada hata payı düzeyi p<0.05 olarak alınmıştır. Birden fazla yanıt gerektiren sorularda frekans sıralaması yapılarak yüzde (%) tekniği kullanılmıştır. Araştırma bulgularına göre; kadınların %28,0‘ının düzenli spor yaptığı, %36,8‘inin düzensiz spor yaptığı, %35,2‘sinin ise spor yapmadığı bulunmuştur. Araştırmaya katılan kadınların %38,4‘ü çalışmakta ve %61,6‘sı çalışmamaktadır. Çalışan kadınların ise %11,3‘ünün düzenli spor yaptığı ve %10,4‘ünün spor yapmadığı bulunmuştur. Kadınların spor konusunda bilinçlendirilerek, spor yapılabilir ortamları arttırmak koşuluyla sporun içine çekmeli ve düzenli spor yapma alışkanlığı topluma kazandırılmalıdır.

The purpose of this research was to create a modern society related to the importance of women‘s sports activities in health, social and culturel fields. It was researched on non-working and working women at private or public institutions and organizations. The research samples represented in total 318 women between the ages of 20 and 40, 122 of whom work and 196 who are housewives.The data which was used in this research, consisted of 34 questions in the form of a questionnaire. The questionnaire was arranged through the expectations of women according to their marital status, whether they work or not, whether they do sport or not. Statistical processes on the data of the research were carried out by using the SPSS (11.0 data) packet program. The X2 (Chi-Square) statistics technique was applied to bring out the difference among the frequency dispersion in the groups and find out if they are important or not. The error numerator level in this research was taken as p< 0.05. According to the finding of the research, it was found that 28% of the women did sport, 36.8% of women sometimes did sport and finally 35.2% of women didn‘t do sport. Of the women who participated in this research, 38.4% of them worked and 61.6% of them didn‘t work. It was found that 11.3% of the working women do sport and 10.4% do not. By analysing this proportion, we can see that women who work do more sport than who do not work. According to the research findings, it has been seen that the factors effecting women‘s sport life have great dimensions. Some of these factors had been found as the following. For example, working and non-working positions, education levels and their jobs, their parents and husband‘s education levels, their salaries,family structure, the family‘snterest in sport, the position of the sport places, the suitable social enuironment, the effects of the enuronment and the close-friends, their weight, time fact and the interest and willing in this topic. Women‘s duties and responsibilities also take great place on doing sport. It must be supplied that by rendering them about sport and creating more sport places, they can be pulled inside sport more easily and efficiently.
The study of factors effecting doing sports of working and nonworking women aged between 20-40
Keywords: Spor Bilimleri; Eğitim, Eğitim Araştırmaları; Aile Çalışmaları